Effluents of Shrimp Farms and Its Influence on the Coastal Ecosystems of Bahía de Kino, Mexico - Ramón H. Barraza-Guardado; José A. Arreola-Lizárraga; Marco A. López-Torres; Ramón Casillas-Hernández; Anselmo Miranda-Baeza; Francisco Magallón-Barrajas; Cuauhtemoc Ibarra-Gámez (The Scientific World Journal)
The impact on coastal ecosystems of suspended solids, organic matter, and bacteria in shrimp farm effluents is presented. Sites around Bahía de Kino were selected for comparative evaluation. Effluent entering Bahia Kino (1) enters Laguna La Cruz (2). A control site (3) was outside the influence of effluents. Water quality samples were collected every two weeks during the shrimp culture period. Our data show that the material load in shrimp farm effluents changes biogeochemical processes and aquatic health of the coastal ecosystem. Specifically, the suspended solids, particulate organic matter, chlorophyll a, viable heterotrophic bacteria, and Vibrio-like bacteria in the bay and lagoon were two- to three-fold higher than the control site. This can be mitigated by improvements in the management of aquaculture systems.